COASTAL COMMUNITY EMPOWERMENT THROUGH PROMOTION OF INDUSTRIAL HOUSEHOLD PRODUCTS PROCESSED FISHERY: IBW IN DISTRICT SUPPA, PINRANG - Maru, Rosmini (Journal of Islam and Science, 2014)
Unitary Republic of Indonesia (NKRI) is a maritime nation potentially sizable marine resources.Pinrang, South Sulawesi is one area in Indonesia, which has a fairly extensive coastal region, with a long coastline.However, this great potential has not been able to provide for the public welfare, increase local revenue, and foreign exchange.Therefore, conducted this activity to the community empowerment in coastal areas in the District Suppa Pinrang through science and technology program for the region (IBW).This activity was conducted over three years beginning in 2012-2014 by using demonstration plots, training, and mentoring.Outcomes of the activities include two aspects, namely: (1) increase the skills to process the results of marine fisheries and conduct better business management;(2) goods of processed fishery and marine Suppa typical form of shredded fish, fish crackers, and fish balls. The results achieved are trained independence and provide insight and knowledge to the public about how to cultivate. and manage the businesses associated with the results of marine fisheries.Finally, these activities have a positive effect for the improvement of people's income, especially groups of partners with increased average income is IRD. 750.000, -. This value is still very low when compared to local minimum wage (UMR), but for the value of coastal communities is very significant, especially for those who previously did not have the income.